Role of Crp to Stratify Severity of Covid- 19 Infection: A Comparison With Chest Computed Tomography - Abdullah, Mohammad Shayekh; Aslam, Azmiree Binte; Sayem, Mohammad (Journal of Dhaka Medical College, 2023)
Background: COVID-19 is the pandemic disease causes severe acute respiratory infection. Tcell mediated responses are activated and responses are initiated by antigen presentation via DCs and macrophages. Immunologically SARS-CoV showed that virus infected lung epithelial cells produced IL-8 in addition to IL-6. A hyperinflammatory environment has been a hallmark of COVID 19 infection and is thought to be a key mediator of morbidity and mortality. C-reactive protein (CRP), an inflammatory marker, can be used in the diagnosis of COVID pneumonia. Purpose: To find out the role of CRP in COVID-19 Infection and comparison with Chest Computed Tomography. Materials and method: This cross sectional prospective study was conducted in Department of Medicine, Dhaka Medical College Hospital, among the 100 patients with symptomatic and positive RT-PCR for SARS-CoV-2. C-reactive protein (CRP) level was compared with HRCT findings. All the information collected in data collection sheet and analyzed using SPSS version-22. Result: Mean age of the patient was 45.2 ± 8.5 years. Fever and cough was commonest presentation, 79.0% and 36.0% of patients respectively. It showed, 27.0% cases were found to have raised CRP where 73.0% had normal level with mean value 14.1 mg/L. Chest HRCT imaging finding revealed, 44% patients had 26–50% lung involvement and 16 patients had 51–75% involvement. In maximum patients (57.0%), chest CT showed single or multiple GGO. HRCT score was significantly higher in patients with raised CRP, and a significant positive significant correlation (r=0.941; p=0.001) between the HRCT scores and CRP level. Conclusion: The rising CRP can aid in predicting COVID-19 pneumonia and significantly correlates with percentage of lung involvement on HRCT in COVID-19 pneumonia. J Dhaka Med Coll. 2021; 30(2) : 136-141